2016
DOI: 10.1590/0101-6628.074
|View full text |Cite
|
Sign up to set email alerts
|

As tecnologias de comunicação na memória dos idosos

Abstract: Resumo O trabalho recorre a depoimentos dos idosos a fim de compreender as transformações sociais ocorridas a partir da interação desse grupo populacional com os meios de comunicação. Por intermédio da dinâmica "Minha primeira vez", cada participante da Uati rememora seu primeiro contato com o aparelho celular, o computador, a TV, o cinema e o rádio. A oficina foi desenvolvida na perspectiva da educomunicação, que se trata de um campo de intervenção social nascido a partir da inter-relação comunicação e educaç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
0
1
0
3
Order By: Relevance
“…Among these, it is observed that software-type technology contributes to health education because, through visual, tactile and auditory stimuli, it exercises memory and helps retention of information 38 . However, in order to increase the effectiveness of interventions with this type of educational technology, it is important to emphasize that the differences in the educational profile of the elderly residents in developed and developing countries, such as Brazil, should be considered, since the low rate of elderly literacy is still a reality, which should be considered in the planning of new technologies for health education for this population 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Among these, it is observed that software-type technology contributes to health education because, through visual, tactile and auditory stimuli, it exercises memory and helps retention of information 38 . However, in order to increase the effectiveness of interventions with this type of educational technology, it is important to emphasize that the differences in the educational profile of the elderly residents in developed and developing countries, such as Brazil, should be considered, since the low rate of elderly literacy is still a reality, which should be considered in the planning of new technologies for health education for this population 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Entre essas demandas, pode-se incluir a de trabalhar com a cognição, pois tanto no envelhecimento normal, quanto no patológico, há mudanças em alguns dos domínios cognitivos, que podem acontecer por diversos fatores, como condições de saúde, atividade mental, nível de instrução, presença ou ausência de treino cognitivo, entre outros (Silva, 2016).…”
Section: Tecnologia E Cogniçãounclassified

Inclusão digital e seus benefícios para os idosos

Benedita.R. da Mota A. Viviani,
Pessoa Parente,
Sadaco Minamizaki Ikuta
et al. 2023
K. GER.
“…Atentando-se às considerações de Silva (2016), é importante valerse dos diversos recursos matemáticos para uma melhor aprendizagem dos idosos. As atividades relativas a raciocínio lógico, por exemplo, possuem o objetivo de, por meio da matemática, estimular a capacidade lógico-dedutiva do idoso, mantendo-o em constante processo de investigação, verificação de hipóteses e mapeamento de soluções.…”
Section: Educação Matemática De Idososunclassified